'A parcel of heart': the business of love in Peregrine Pickle. (2016) - Breashears, Caroline
McCloskey (2010) has linked modern economic growth with a change in rhetoric about the bourgeoisie and virtues such as prudence. She locates this shift in the 17th and 18th centuries in northern Europe. I build on that argument in analysing a unique novel published on the cusp of the industrial revolution - Tobias Smollett's The Adventures of Peregrine Pickle. In which Are Included, Memoirs of a Lady of Quality (2014) - which focuses on two representatives of the rising bourgeoisie: a real woman (Lady Vane) and her fictional counterpart, Peregrine. I argue that, through tracing their adventures, this work illuminates the transition in rhetoric about prudence and the bourgeoisie: it does not simply depict the bourgeoisie as dignified but shows how people negotiated the meanings of key terms such as 'gentleman', 'prudence', 'love', and 'contract'.